2019
DOI: 10.3390/en12244619
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Galloping Piezoelectric Energy Harvester with V-Shaped Groove in Low Wind Speed

Abstract: A square cylinder with a V-shaped groove on the windward side in the piezoelectric cantilever flow-induced vibration energy harvester (FIVEH) is presented to improve the output power of the energy harvester and reduce the critical velocity of the system, aiming at the self-powered supply of low energy consumption devices in the natural environment with low wind speed. Seven groups of galloping piezoelectric energy harvesters (GPEHs) were designed and tested in a wind tunnel by gradually changing the angle of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 39 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…The over-bar denotes the complex conjugate. Substituting the zeroth-order solutions into the right hand side of the first order equations (17)(18)(19)(20) and expanding the equations, it can be observed that frequency modes with frequency ratio of 1:1 are coupled via the oscillating wake force and the linear terms of magnetic force.…”
Section: Analytical Solutions Based On Methods Of Multiple Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The over-bar denotes the complex conjugate. Substituting the zeroth-order solutions into the right hand side of the first order equations (17)(18)(19)(20) and expanding the equations, it can be observed that frequency modes with frequency ratio of 1:1 are coupled via the oscillating wake force and the linear terms of magnetic force.…”
Section: Analytical Solutions Based On Methods Of Multiple Scalementioning
confidence: 99%
“…A general GPEH is composed of a cantilever beam attached with piezo patch and a cross-section asymmetric bluff body fixed on its free end. To further improve energy harvesting efficiency and reduce the critical wind speed, some researchers have been devoting their efforts on optimizing the cross-section of bluff body [16][17][18][19][20][21], exerting synergy effect by combining aerodynamic phenomena (VIV, galloping) [22][23][24][25] and increasing the degrees of freedom (DOF) [26,27]. Lan et al [26] proposed lumped parameter models for two structural configurations with different bluff bodies under aerodynamic force.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been done to consider the piezoelectric energy harvester when a cubic bluff body is attached to the tip of the beam. The aerodynamic force in this category of works is due to galloping phenomena (Ewere and Wang, 2014;Rezaei and Talebitooti, 2019;Seyed-Aghazadeh et al, 2020;Wang et al, 2020;Zhao et al, 2012Zhao et al, , 2016Zhao et al, , 2019. Unlike VIV that exhibits large amplitudes only when the vortex-shedding frequency is near the structure's natural frequency (lock-in or synchronization), the galloping phenomenon exhibits large amplitudes after a critical speed.…”
Section: Introductionmentioning
confidence: 99%
“…These works are mainly based on the beam optimization of mathematical functions of beams, but in fact, the global optimization analysis is more reasonable for structural design. In our previous study, we used a combination of wind tunnel experiments and data-driven methods to optimize the crosssectional shape of the bluff body (Zhao et al, 2019). Based on these research results, the geometry of the piezoelectric cantilever beam is globally optimized in this study.…”
Section: Introductionmentioning
confidence: 99%